If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(7x + -3) = 10 Reorder the terms: 5(-3 + 7x) = 10 (-3 * 5 + 7x * 5) = 10 (-15 + 35x) = 10 Solving -15 + 35x = 10 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '15' to each side of the equation. -15 + 15 + 35x = 10 + 15 Combine like terms: -15 + 15 = 0 0 + 35x = 10 + 15 35x = 10 + 15 Combine like terms: 10 + 15 = 25 35x = 25 Divide each side by '35'. x = 0.7142857143 Simplifying x = 0.7142857143
| -35-5x=4x+19 | | 4=0.167t-0.67 | | -2(w+6)+6w=4(w-3) | | 8-9x=66-23x | | 2(w+2)+w=3(w-1)+6 | | 6(y+1)-9=4(y-1)+2y | | 165-6x=5x+22 | | 2-3y=1 | | 16x^4-24x^2+9=0 | | -4(y+4)=3(y+4)+7 | | x+2-3x=-5x+8 | | 2(y-1)-3y=3(y-6) | | .6+.25x-.33=.75x | | 4(95-8x)=x-15 | | x+1=3x+3 | | 4(y+1)-7=3(y-1)+y | | x+1=x+3 | | -5x+6x-5=5x+4-5x | | 4y^2+12y+5=0 | | 12x-31=3x-4 | | 3a+2=-6-d | | .33+2=5 | | x^2-3xy+2y^2=4 | | 25=9x-74 | | x^2+5x-88= | | (n^6)-1=3 | | 7+x=19 | | 6x+10=363x | | 5(3x+1)=7(x+1) | | 6(x+5)=23-x | | 4(x+1)=x+10 | | 20=11+4(x+1) |